Avaliação do efeito da pregabalina pré-operatória para analgesia e concentrações plasmáticas de interleucina 6, 8 e 10 após nefrectomia por lombotomia. Estudo clínico randomizado duplo-encoberto. - Santiago, Ana Ellen de Queiroz [UNIFESP] (2018)
Background and Objectives: Pregabalin is an anticonvulsant, modulator of alpha2delta subunit of calcium channels, promoting inhibition of excitatory neurotransmitters release. It is possible that the pre-operatory administration of pregabalin promotes analgesic effect and act on release of cytokines. The objective of the study was to evaluate the analgesic effect of pregabalin after nephrectomy. Methods: A randomized double-blind study was performed in 40 patients submitted to nephrectomy for kidney transplantation. Group-1 patients received 300mg of pregabalin before the surgery and group-2 received placebo. Epidural anesthesia was performed with 15 mL of 0.5% ropivacaine followed by general anesthesia with fentanyl (3 μg.kg-1), propofol, atracurium, 50% oxygen, without nitrous oxide, and sevoflurane. There were evaluated: pain intensity after 6 and 24 hours; pain threshold with algometer periincisional and in the tennar eminence of the hand; dosage of IL 6, 8 and 10 before surgery and 6 and 24 h after a surgical incision; number of patients needing complementation; time for complementation; supplemental analgesic dose (tramadol); and adverse effects. Results: Pain intensity was lower after 24h with pregabalin, in G1; there was no difference of pain threshold with algometer in the tennar region; There were no differences between groups about IL-6, IL-8 and IL-10, after 6 and 24h; There were no differences in number of patients needing complementation, and dose of analgesic. There was no difference in the incidence of adverse effects (nausea, vomiting, headache, dizziness, agitation and pruritus). Conclusions: The administration of a single dose of 300mg of pregabalin before lombotomy decreased the intensity of pain after 24h; did not reduce supplemental analgesic dose; did not change the concentration of IL6, IL8 and IL10; did not change the incidence of adverse effects.